1999
DOI: 10.1108/00070709910261936
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance and the consumer

Abstract: In recent years, quality assurance schemes have grown considerably in number and scope. Several useful benefits have been claimed for them including their value as marketing advantages. However, there appears to be a paucity of published research to support this claim. This paper, therefore, seeks to substantiate the claim that quality assurance schemes represent useful marketing advantages as well as determining the magnitude of the advantage. The study is based on conjoint analysis as it is argued that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 20 publications
2
47
0
2
Order By: Relevance
“…Walley et al (1999) revealed how consumers valued quality assurance labels as an important indicator of meat quality. Consumers preferred to purchase meat products which were quality assured rather than meat which was not.…”
Section: Insert Table 7 About Here --------------------------------mentioning
confidence: 99%
“…Walley et al (1999) revealed how consumers valued quality assurance labels as an important indicator of meat quality. Consumers preferred to purchase meat products which were quality assured rather than meat which was not.…”
Section: Insert Table 7 About Here --------------------------------mentioning
confidence: 99%
“…Among these instruments are the use of certified labels or seals that guarantee determined differentiating attributes of a product (Oyarzún and Tartanac, 2002). The use of quality labels or seals has brought a "new" attribute into the consumer choice process at the moment of purchasing (Walley et al, 1999). At the same time, the instruments of quality management, such as labels and seals, have been able to transform quality aspects to actively sought food attributes, facilitating the consumer purchasing process (Fotopoulos and Krystallis, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…On product differentiation reported that the Halaal symbolization is considered to be point of difference in the retail environment. This symbol has brought positive perceptions regarding the product and serves as a positive attribute which leads to Halaal food preferences [51] . The Halaal symbol is considered as a quality management symbol, which makes it one of the actively sought attribute by the consumer in their buying process [18] .The increasing acceptance of Halaal products in non-Muslim countries has also been confirmed by the studies of [9] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…A significant finding is that Halaal symbolized foods are considered to be superior in quality as compared to non-Halaal [11] . In Malaysian context and reported that Malaysian consumers consider Halaal logo issued by JAKIM to be the quality indicator [51] . Muslim consumers value the products with Halaal logo than any other certification [50] .…”
Section: Literature Reviewmentioning
confidence: 99%